New Technology Focus: Smart Polymer in Vascular Surgery - Ross Milner (Vascular and Endovascular Review, 2022)
A new smart polymer technology developed by Shape Memory Medical is available to endovascular specialists. The shape memory polymer is incorporated into vascular plugs and coils. Dr Ross Milner, a vascular surgeon at University of Chicago Medicine, gives his perspective on the properties of the shape memory polymer and how smart polymer devices may be used in vascular surgery.